2008
DOI: 10.1063/1.2913167
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent photoionization of azulene: Competition between ionization and relaxation in highly excited states

Abstract: Pump-probe photoionization has been used to map the relaxation processes taking place from highly vibrationally excited levels of the S 2 state of azulene, populated directly or via internal conversion from the S 4 state. Photoelectron spectra obtained by 1+2' two-color time-resolved photoelectron imaging are invariant (apart from in intensity) to the pump-probe time delay and to pump wavelength. This reveals a photoionization process which is driven by an unstable electronic state (e.g. doubly excited state) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…This means that, in the process illustrated in Scheme 1 (for azulene, but it may be generic for polyaromatic molecules 22 ), the IC step S 1 f S 0 becomes faster and faster with an increasing MW. Then, beyond a certain MW value, essentially all of the S 1 state will be consumed in S 1 f S 0 IC and the molecule will not be detectable in LIMS.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This means that, in the process illustrated in Scheme 1 (for azulene, but it may be generic for polyaromatic molecules 22 ), the IC step S 1 f S 0 becomes faster and faster with an increasing MW. Then, beyond a certain MW value, essentially all of the S 1 state will be consumed in S 1 f S 0 IC and the molecule will not be detectable in LIMS.…”
Section: Discussionmentioning
confidence: 98%
“…In an elegant, detailed study 22 published recently on the time-dependent photoionization of azulene and the competition between ionization and relaxation in highly excited states, it was shown that the phenomena observed in the study may be quite generic in polycyclic aromatic molecules. A detailed consideration of all of the results and their interpretations lies outside the scope of the present paper, and only the relevant salient features of this study will be discussed here, as follows:…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The Rydberg states, due to their peculiar strong propensity for ∆v = 0 ionization, are also expected to be distinct from the other contributions to the kinetic energy and angular distributions of the photoelectrons. 33,36 The excitation schemes for all wavelength combinations are summarized in Figure 1. One THG photon (267 nm) is enough to probe the wave packet dynamics onto D 0 or at the threshold of D 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A decay rate increases exponentially with vibrational excitation in the initial state but not indefinitely. 36 A plateau is reached when the density of vibrational levels in the initial state is so large that the entropy of the initial state (M*) can no longer be neglected. 42 This corresponds to a wavepacket in which the vibronic coupling becomes more and more diluted in the uncoupled vibrational modes.…”
Section: Discussionmentioning
confidence: 99%